1983
DOI: 10.1111/j.1365-246x.1983.tb01906.x
|View full text |Cite
|
Sign up to set email alerts
|

A note on the isostatic compensation and origin of King's Trough

Abstract: Summary. The depth and seismic source parameters of the three largest reservoir-induced earthquakes associated with the impoundment of Lake Kariba, Africa, were determined, using a moment tensor formalism of the generalized inverse technique. The events, characterized by mb > 5.5, consisted of the foreshock and main event (0640 and 0901 GMT, 1963 September 23) and the principal aftershock (0703 GMT, 1963 September 25). From the analysis of analogue rift valley source crustal models, a threelayer over a half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…But the main tectonic events responsible for the formation of its troughs and basins probably occurred much later, during the Miocene. This is in agreement with a post-early Oligocene (< 30 Ma) formation of King's Trough, as suggested by Louden (1983), and an initial hot-spot origin for the King's Trough High.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But the main tectonic events responsible for the formation of its troughs and basins probably occurred much later, during the Miocene. This is in agreement with a post-early Oligocene (< 30 Ma) formation of King's Trough, as suggested by Louden (1983), and an initial hot-spot origin for the King's Trough High.…”
Section: Discussionsupporting
confidence: 91%
“…Grimaud et al (1983) suggested a leaky-transform origin for King's Trough through a tectonic association with the Pyrenean orogenic phase. Louden (1983) concluded, however, through a spectral analysis of gravity and topographic profiles, that formation of the Trough itself postdated the formation of the Pyrenees, unless that orogeny continued well after 38 Ma, the late Eocene.…”
Section: Introductionmentioning
confidence: 99%
“…It is very likely that the two are interrelated and thus correspond to the extensional phase (40-24 Myr) when King's Trough became part of the plate boundary between Eurasia and Iberia (Roest & Srivastava 1991). Based on the analysis of a gravity and bathymetric profile, Louden (1983) suggested that King's Trough was formed no earlier than 30Ma. This would suggest that the major part of the present-day topography of King's Trough was created in the later stages of extension across the plate boundary.…”
Section: Formation Of King's Troughmentioning
confidence: 98%
“…7) 1991). Based on the analysis of a gravity and bathymetric profile, Louden (1983) suggested that King's Trough was formed no earlier than 30Ma. This would suggest that the major part of the present-day topography of King's Trough was created in the later stages of extension across the plate boundary.…”
Section: Formation Of King's Troughmentioning
confidence: 99%
See 1 more Smart Citation